Invariances and diversities in the evolution of manufacturing industries - Giulio Bottazzi; Elena Cefis; Giovanni Dosi; Angelo Secchi (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2003)
In this work we explore some basic properties of the size distributions of firms and of their growth processes both at aggregate and disaggregate levels. First, we investigate which properties of firm's size distributions and growth dynamics are robust under disaggregation. Second, at a disaggregate level, we try to identify those features which are generic and hold across all or most of the considered three digit sectors distinguishing them from sector-specific ones. Concerning firm growth, we mainly focus on the characterization of the distribution of growth rates, studying, again, the possible differences between sectors and between levels of aggregation. Finally, we begin to explore the relations between measures of size distributions and the nature of the underlying growth processes and discuss some admittedly unresolved puzzles.
Keywords: 330; Firm Size Distribution; Firm Growth; Laplace Distribution; Unternehmenswachstum; Industrie; Betriebsgrößenstruktur; Italien